Should I stay or leave? The effect of remittances in the sub-Saharan region - Dachen Sheng; Suhayb Abdi Hussein; Clement Likomba (Cogent Social Sciences)
This research provides empirical evidence that the socioeconomic improvement effect of remittances is dependent on the local status in recipient countries. Using regression and the two-stage least squares (2SLS) method, we first show that remittance size is associated with migration travel intentions. Second, the article demonstrates that in an unstable environment, even though remittances have a positive immediate effect, the influence of remittances on other longer-term proxies is significantly negative. Such finding is different compared with most of the current studies on remittance and its effects. The reason may be attributed to the departure of skilled workers from their home country decreases local socioeconomic development. The remittances and foreign connections help people with migration intention to move out and more easily settle in destination countries. Finally, we propose a potential policy direction to encourage local residents to directly consume or invest remittances in local society to improve development and decrease migration intentions.